Dual‐Wavelength Carpet Cloak Using Ultrathin Metasurface. Issue 14 (26th April 2018) - Yang, Jianing; Huang, Cheng; Wu, Xiaoyu; Sun, Bo; Luo, Xiangang
Abstract: Ultrathin metasurfaces pave an encouraging way for invisibility carpet cloaks on account of their excellent electromagnetic wavefront manipulation. However, the current metasurface‐based carpet cloaks operate at only one wavelength and are limited by their narrow bandwidth. Here, a dual‐wavelength carpet cloak using a two‐layer metasurface at the microwave frequencies is proposed. By individual design of phase compensation at each layer of the metasurface, the proposed cloak can restore the scattering behaviors of a flat conducting plane at different frequencies. Both simulation and experimental results demonstrate that the cloaking effects are realized at 6.1 and 10.2 GHz. In addition, it is found that the cloak is polarization‐insensitive at above two frequencies. The proposed design can be also scaled to the terahertz and optical domain. Abstract : A dual‐wavelength carpet cloak using a two‐layer metasurface is proposed. By individually controlling the local phase distribution at each layer of the metasurface, the carpet cloak can realize the electromagnetic shapes of a metallic flat plate at two frequency bands under both transverse electric (TE) and transverse magnetic (TM) polarizations. Moreover, it can also generate other different electromagnetic shapes through redesigning the phase compensation.